Chronic intermittent ethanol and lipopolysaccharide exposure differentially alter Iba1-derived microglia morphology in the prelimbic cortex and nucleus accumbens core of male Long-Evans rats - Siemsen, Benjamin M. (J Neurosci Res, 2020)
Accumulating evidence has linked pathological changes associated with chronic alcohol exposure to neuroimmune signaling mediated by microglia. Prior characterization of the microglial structure-function relationship demonstrates that alterations in activity states occur concomitantly with reorganization of cellular architecture. Accordingly, gaining a better understanding of microglial morphological changes associated with ethanol exposure will provide valuable insight into how neuroimmune signaling may contribute to ethanol-induced reshaping of neuronal function. Here we have used Iba1-staining combined with high-resolution confocal imaging and 3D reconstruction to examine microglial structure in the prelimbic (PL) cortex and nucleus accumbens (NAc) in male Long-Evans rats. Rats were either sacrificed at peak withdrawal following 15 days of exposure to chronic intermittent ethanol (CIE) or 24 hr after two consecutive injections of the immune activator lipopolysaccharide (LPS), each separated by 24 hr. LPS exposure resulted in dramatic structural reorganization of microglia in the PL cortex, including increased soma volume, overall cellular volume, and branching complexity. In comparison, CIE exposure was associated with a subtle increase in somatic volume and differential effects on microglia processes, which were largely absent in the NAc. These data reveal that microglial activation following a neuroimmune challenge with LPS or exposure to chronic alcohol exhibits distinct morphometric profiles and brain region-dependent specificity.